A Bibliometric Analysis on Sustainable Tourism In 2023 - Awaloedin, Dipa Teruna; Putri, Ananda Fadila; Ekania, Nadhira; Pradini, Gagih; Agustiani, Fitri (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Sustainable tourism refers to the type of tourism in which the environmental, social, and economic impacts of tourism are taken into account, and where relevant adjustments are made to minimize these negative consequences. In sustainable tourism, we consider the needs of travelers, but also the needs of host communities, local businesses, and nature. Sustainable tourism is a concept that aims to minimize the negative impact of tourism on the environment, society, and economy. This involves responsible use of resources, preservation of local culture and traditions, and increased economic benefits for local communities. Sustainable tourism seeks to balance the needs of tourists with the needs of destinations, ensuring that future generations can enjoy the same attractions and experiences. It focuses on long-term sustainability, promoting environmentally friendly, socially inclusive, and economically viable practices. By implementing sustainable tourism practices, we can contribute to preserving our planet while still enjoying the beauty and diversity it has to offer. Based on network visualization the most dominant terms (often appearing) are "communities based tourism" and "sustainable tourism". When viewed from the Overlay Visualization, the topic of "communities-based tourism" shows the latest trends in research related to "rural communities"